Credit risk management based on harmonious cultural values to support microfinance institution performance in Indonesia - I Putu Astawa; Raka Sukawati; Christantius Dwiatmadja (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Credit risk is important in developing the performance of a microfinance institution. The aim of this research was to analyze credit risk through a harmonious cultural approach to improve financial performance. Qualitative approach was used to explore the practice of harmonious culture in managing credit risk. The result of the qualitative study would be utilized to design a questionnaire for quantitative test. Ninety-four (94) companies were selected as the samples by using Slovin Method. The result of the qualitative study explained that harmonious culture-based credit risk was influenced by loan quality, collateral quality, customary rules, traditional leaders, and the belief in karma phala law. Quantitatively, it was found that loan quality, collateral quality, customary rules, traditional leaders, and the belief in karma phala law simultaneously influenced the financial performance. The research result had an implication to risk management in improving financial performance. It could also be used as a new strategy for managers to maintain good relationship with customers.
Keywords: G21; G23; G32; M14; 650; credit risk; harmonious culture; performance